2008
DOI: 10.1515/sg-2008-0050
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Early Growth Characteristics of Two Populations of Wild Service Tree (Sorbus torminalis (L.) Crantz) and Their Interrelationship

Abstract: This study was performed in order to compare two wild service tree populations (Sorbus torminalis (L.) Crantz) for their early growth and to find useful vegetative characteristics to be used in indirect selection of fast and tall growing trees of the species in the field. We used phenotypic and genotypic correlation coefficients estimated on data from 30 three-year old seedlings of each 40 randomly selected adult trees. Assuming genetic differences between the trees sampled, path analysis was performed on geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…As expected from a largely outbreeding tree, S. torminalis has been found to be genetically diverse within and between populations with strong gene flow (Demesure et al 2000a;Oddou-Muratorio et al 2001aBednorz & Krzakowa 2002;Bednorz, Myczko & Kosi nski 2004Oddou-Muratorio, Klein & Austerlitz 2005;Rasmussen & Kollmann 2004bHoebee et al 2006Hoebee et al , 2007Angelone et al 2007;Espahbodi et al 2008, Jankowska-Wroblewska et al 2016. Sorbus torminalis in Britain has a lower genetic diversity than the other two common sexually reproducing diploid species, S. aria and S. aucuparia (Proctor, Proctor & Groenhof 1989;Chester et al 2007) and lower than S. torminalis in mainland Europe: Chester et al found that pollen exchange shows two main patterns: preferential mating between neighbouring trees from local pollen dispersal with a mean of 6 pollen donors providing the pollen cloud around a given tree, and also long-distance pollen movement of up to 2Á5 km.…”
Section: Floral and Seed Charactersmentioning
confidence: 72%
See 1 more Smart Citation
“…As expected from a largely outbreeding tree, S. torminalis has been found to be genetically diverse within and between populations with strong gene flow (Demesure et al 2000a;Oddou-Muratorio et al 2001aBednorz & Krzakowa 2002;Bednorz, Myczko & Kosi nski 2004Oddou-Muratorio, Klein & Austerlitz 2005;Rasmussen & Kollmann 2004bHoebee et al 2006Hoebee et al , 2007Angelone et al 2007;Espahbodi et al 2008, Jankowska-Wroblewska et al 2016. Sorbus torminalis in Britain has a lower genetic diversity than the other two common sexually reproducing diploid species, S. aria and S. aucuparia (Proctor, Proctor & Groenhof 1989;Chester et al 2007) and lower than S. torminalis in mainland Europe: Chester et al found that pollen exchange shows two main patterns: preferential mating between neighbouring trees from local pollen dispersal with a mean of 6 pollen donors providing the pollen cloud around a given tree, and also long-distance pollen movement of up to 2Á5 km.…”
Section: Floral and Seed Charactersmentioning
confidence: 72%
“…Similarly, aspect is only important in hot, dry areas such as Iran where it occurs on north and north‐east facing slopes (Espahbodi et al . ). Sorbus torminalis is very wind firm and rarely suffers from wind‐throw (Kausch‐Blecken von Schmeling ).…”
Section: Habitatmentioning
confidence: 97%
“…As a comparison, the average height of 4-year-old seedlings of this species in progeny-provenance plots from two locations in Poland amounted to about 92 cm (Sulkowska & Wojda 2015), whereas in Iran the height of 3-year old seedlings was 50 cm on average (Espahbodi et al 2008). However, it seems that the significant differences observed in the growth rate of the youngest seedlings (up to about 5-8 years) progressively flattens out during their development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the growth and survival rate of wild service tree seedlings cultivated in nurs- eries or progeny-provenance plots (Espahbodi et al 2008, Sulkowska & Wojda 2015, but no data are available so far on the spontaneous regeneration of such species in the forest, with the exception of Schüte (2001) who investigated the growth and shade tolerance of root suckers in a natural population in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the amount of seeds is first of all a function of the number, the age, the size and the physiological condition of the trees in the stand. Espahbody et al [31] informed that more fertile seeds in terms of quality and quantity were obtained from middle aged trees. Although Fennessy [32] said that high quality fertile seeds increased from higher age to middle age, especially the beech and the oak tree, in this study, it was apparent that tree ages of beech merely affected the seed germination positively.…”
Section: The Impact Of Tree Agementioning
confidence: 99%